Improvement of Physical Properties for KNN‐based Ceramics by Modified Two‐Step Sintering. Issue 3 (3rd January 2014) - Zhang, Jialiang; Qin, Yalin; Gao, Yong; Yao, Weizeng; Zhao, Minglei; Damjanovic, D.
<x xml:space="preserve">Abstract</x> A modified two‐step sintering (MTSS) technique was attempted to fabricate dense (K, Na)NbO3‐based lead‐free ceramics through the solid‐state reaction route. (K0.50Na0.50)0.98Li0.02(Nb0.795Ta0.18Sb0.025)O3 and (K0.45Na0.55)0.98Li0.02Nb0.77Ta0.18Sb0.05O3 were chosen as the test chemical compositions, and high relative density values over 97.5% were successfully obtained in their corresponding ceramics. Consequently, the d33 values were enhanced considerably and reached 353 and 436 pC/N, respectively. The latter d33 value is a record one ever achieved in the (K, Na)NbO3‐based ceramic materials so far. Furthermore, observation analyses of microstructure and domain patterns were carried out and showed that partial depoling occurs more easily in large grains than in small ones. In particular, it was found that the (K0.50Na0.50)0.98Li0.02(Nb0.795Ta0.18Sb0.025)O3 ceramic densified by MTSS has a quite uniform grain‐size distribution with comparatively small grains and exhibits the very excellent time‐aging stability. The study results suggest that microstructure with high relative density and suitably suppressed grain sizes is desirable for further acquiring the superior KNN‐based ceramics of both excellent piezoelectric properties and good depoling stabilities.